Application of water to the mushroom colonized compost prior the addition of the casing layer - Zied, Diego Cunha; Marinsek, Bruno; Dias, Eustáquio Souza; Rinker, Danny Lee; Caitano, Cinthia Elen Cardoso [UNESP]; Da Silva Alves, Lucas [UNESP]; Pardo-Gimenez, Arturo (UNESP - Universidade Estadual Paulista, 2024)
The mushroom Agaricus bisporus is produced on all the continents. To increase yield and efficiency during the process of mushroom production, and reduce costs and size of the mushroom farm, production of fully colonized compost in specialized chambers (a.k.a. Phase III compost) evolved. One challenge in this technology is achieving appropriate substrate moisture. Average moisture content at the end of pasteurization and conditioning in this kind of chamber is approximately 60%. The aim of this study was evaluate the effect of the addiction of different levels of irrigation before casing onto the surface of A. bisporus PIII compost. Five irrigation rates were applied to the surface of the colonized compost: T1 - control (60% moisture); T2 - 200 ml box-1 (62% moisture); T3 - 400 ml box-1 (63.5% moisture); T4 - 800 ml box-1 (67% moisture); T5 - 1.600 ml box-1 (74% moisture); T6 - 3.200 ml box-1 (87% moisture). Mushroom yield increased with increasing moisture levels in the compost, obtaining higher values for the treatment 3200 ml box-1. The application of water to the colonized compost can become a low cost practice in a mushroom commercial production.
Keywords: Agaricus bisporus; button mushroom; compost phase III; high technology; yield